El club de la mariposa - Wilson, Jacqueline (Tres edades, 2016)
Tina is a triplet, but she's always been the odd one out. Her sisters Phil and Maddie are bigger and stronger and better at just about everything. Luckily, they look after teeny-tiny Tina wherever they go -- but when the girls start in scary, super-strict Miss Lovejoy's class, they're split up, and Tina has to fend for herself for the first time. Tina is horrified when she's paired up with angry bully Selma, who nobody wants to be friends with. But when Miss Lovejoy asks them to help her create a butterfly garden in the school playground, Tina discovers she doesn't always need her sisters -- and that there's a lot more to Selma than first meets the eye. A beautiful, heartwarming story about friendship, confidence and becoming your own person.